Problems and prospects of development of accounting in current business environment - Malashenko, Natalia (My University, 2012)
It is necessary to critically analyze all available methodological tools of accounting and components (elements) of its method in terms of their compliance with the market economy and opportunities for further modification. Треба критично аналізувати всі наявні методологічні інструменти обліку та компоненти (елементи) його метод з точки зору їх відповідності ринкової економіки і можливостей для подальшої модифікації.
Keywords: бухгалтерський облік; ділове середовище; перспективи розвитку; business environment; development prospects; accounting